(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Rice production in Asia must increase continuously to feed people. While the water shortage in rice cultivation in Asia has yet to be completely evaluated, there is evidence that water quality and availability decreases threaten the sustainability of the irrigated rice system. Drought is one of the major restrictions of high Rain-fed rice yields. Food safety and environmental health in Asia must explore ways for growing more rice with less water. This research examines the whole rice production plan of the International Rice Research Institute (IRRI), which includes genetics, breeding, and integrated resource management. Irrigation techniques such as saturated soil cultivation and alternative weathering and dewatering will significantly reduce waste dumping while increasing water yield. Another innovative method is being investigated without sacrificing production to improve water productivity. The C4 route is integrated into rice to increase output per unit of transpired water, utilize genetic engineering to improve dry tolerance and produce "aerobic rice" for good and safe yields on unflooded soils.